The Improvement Of Safety Analysis Form (HIRARC) For Manual Tamping Works In Keretapi Tanah Melayu Berhad (KTMB): - - BIN SULKIFLI, MOHAMAD ARIF (Progress in Engineering Application and Technology, 2023)
Maintenance activities consist of routine servicing or heavy mechanical maintenance, such as tamping works[1]. These critical aspects must be completed properly with full concentration and dedication by the workers who have been assigned the task of maintaining the railway track to prevent injuries and accidents. In this study, the existing safety analysis form (HIRARC) of manual tamping works in KTMB was improve to make sure to ensure it meets current needs. HIRARC is a systematic approach to identifying and controlling hazards in the workplace. It is a valuable tool for improving workplace safety and reducing the risk of accidents and injurie. analysis and review for tamping manual works will be carried out to see the current safety situation and to identify the hazards that exist when these works are carried out. The level of risk will use risk assessment where likelihood and severity will be used to get the risk level value. Results of the safety review, Improvements will be made to the existing HIRARC form with the addition of resources of hazard. This enhancement will make the HIRARC form more detailed and easier to determine the control measure to be used. The improved HIRARC will be brought to the interview session for validation and review by KTMB track engineering staff.